Reliability of graphite furnace atomic absorption spectrometry as alternative method for trace analysis of arsenic in natural medicinal products - Khalid, Reem Saadi; Abul Bashar Mohammed, Helaluddin; Alaama, Mohamed; Kasmuri, Abdul Razak; Abbas, Syed Atif (Pharmacotherapy Group,University of Benin, 2016)
Purpose:To evaluate the comparative efficiency of graphite furnace atomic absorption spectrometry (GFAAS) and hydride generation atomic absorption spectrometry (HGAAS) for trace analysis of arsenic (As) in natural herbal products (NHPs). Method:Arsenic analysis in natural herbal products and standard reference material was conducted using atomic absorption spectrometry (AAS), namely, hydride generation AAS (HGAAS) and graphite furnace (GFAAS).The samples were digested with HNO 3 –H 2 O 2 in a ratio of 4:1 using microwave-assisted acid digestion. The methods were validated with the aid of the standard reference material 1515 Apple Leaves (SRM) from NIST Results: Mean recovery of three different samples of NHPs, using HGAAS and GFAAS, ranged from 89.3 - 91.4 %, and 91.7 - 93.0 %, respectively. The difference between the two methods was insignificant. A (P= 0.5), B (P=0.4) and C (P=0.88) Relative standard deviation (RSD) RSD, i.e., precision was 2.5 - 6.5 % and 2.3 - 6.7 % using HGAAS and GFAAS techniques,respectively. Recovery of arsenic in SRM was 98 and 102 % by GFAAS and HGAAS, respectively. Conclusion: GFAAS demonstrates acceptable levels of precision and accuracy. Both techniques possess comparable accuracy and repeatability. Thus, the two methods are recommended as an alternative approach for trace analysis of arsenic in natural herbal products.